Innovative Extension Model(s) in promoting Climate Change Adaptation in Agriculture - N. Balasubramani; Sreenath Dixit (Journal of Agricultural Extension Management, 2017)
Increasing climate variability would aggravate the problem of food and nutritional security of the growing population in India. Concerted efforts are required for mitigation and adaptation to reduce the vulnerability of Indian agriculture to the adverse impacts of climate change and make it more resilient. The Government of India has taken several steps to address climate change and reduce the vulnerability of farmers to adverse impacts of climate change. Various extension models are being adopted by different public and private organizations in dissemination of climate resilient technologies and to enhance the preparedness of the farmers. A few such innovative models are discussed in the paper. A strong extension network and appropriate extension methods, can help enhance the capability of farmers towards adaptation of climate resilient technologies say the authors.